(2-5q)=(-3)

Simple and best practice solution for (2-5q)=(-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2-5q)=(-3) equation:



(2-5q)=(-3)
We move all terms to the left:
(2-5q)-((-3))=0
We add all the numbers together, and all the variables
(-5q+2)-((-3))=0
We add all the numbers together, and all the variables
(-5q+2)+3=0
We get rid of parentheses
-5q+2+3=0
We add all the numbers together, and all the variables
-5q+5=0
We move all terms containing q to the left, all other terms to the right
-5q=-5
q=-5/-5
q=1

See similar equations:

| (13x+13)+(6x+3)=180° | | 6a+12+10=8-a+27 | | 3x-1/3=x/5+2 | | 4(x+2)=7x-3(x-2) | | -7(-3+3n)=7(-4n+1) | | 11w-10=-4+35 | | 3x+12=7x-18 | | 1/3(x+1)+2=1/6(3x-5) | | 4(3x-5)+2=5(2x-7)+x | | 4(x+2)=7x-3(x-2 | | 15-(4*g)=-33 | | -3k+7k=0 | | -90=-6(x+5) | | 5x+6-9x+5=-4x+11 | | -3m+3=8 | | 6x-30=x+36 | | -2=4-(-7y+1)+5(8+2y) | | 2(4r+6)=2÷3(12r+18) | | 11x-6=3x+8x | | (3/4)n+16=2-1/8n | | 2(y-7)-1=2(-6y+6)-y | | 15+18-16=8-16+5a+5 | | 10x-5=6x-25 | | 3(w+1)-2(w+2)=11 | | 4x+1+7x-17=3x | | -26=7u+9 | | 2÷5h-7=12÷5h-2h+3 | | x+135+80+45=360 | | 175x-100x+52,525=55,000-200x | | 5a-4=2a+6 | | 2.5(x+2)-3=1.5(x-2) | | 23+n=19 |

Equations solver categories